Unconventional computation and natural computation : 14th International Conference, UCNC 2015, Auckland, New Zealand, August 30-September 3, 2015, Proceedings /: 14th International Conference, UCNC 2015, Auckland, New Zealand, August 30-September 3, 2015, Proceedings. (2015) - Unknown
No abstract available